High Rates of High-Grade Cervical Dysplasia in High-Risk Young Women With Low-Grade Cervical Cytology. Issue 3 (July 2018) - Daily, Laura R.; Erickson, Britt K.; Pasko, Daniel N.; Straughn, J. Michael; Huh, Warner K.; Leath, Charles A.
Abstract : Objective: The aim of the study was to determine rates of cervical intraepithelial neoplasia (CIN) 2 or greater in high-risk, racially diverse, young women with low-grade cytology. Materials and Methods: After institutional review board approval, a cross-sectional study of 21- to 24-year-old women with low-grade cytology (atypical squamous cells of undetermined significance, high-risk human papillomavirus+, low-grade squamous intraepithelial lesion, or human papillomavirus+ only) managed with colposcopy at our university-based clinic between May 2011 and April 2013 were identified. Demographics and pathologic data were collected including age, race, parity, smoking status, screening history, and histology. Student t test and χ 2 tests were used to compare women with and without CIN 2 or 3. Univariate analysis was performed with demographic data. Results: One thousand fifty-eight women with a mean (SD) age of 22.5 (1.1) were included. Most patients (59.5%) were parous, 36.1% were smokers, and most (52.9%) were black. These patients were considered high risk because of their lower socioeconomic status, minority status, lack of insurance, or having Medicaid and therefore had limited access to preventative health care. Based on colposcopy, the prevalence of CIN 2+ was 19.1%: 13.9% (95% CI = 11.9–16.1) CIN 2 and 5.1% (95% CI = 3.9–6.6) CIN 3. There was an overall prevalence of 4.7% (95% CI = 3.7%–6.3%) of CIN 3 from excisional pathology from the 157 of 185 patients who returned for a recommended excisional procedure. Smoking (odds ratio = 1.64, 95% CI = 1.2–2.25) and a history of high-grade cytology (odds ratio = 2.06, 95% CI = 1.02–4.01) were associated with CIN 2/3. Conclusions: High prevalence of CIN 2/3 in young women with low-grade cervical cytology in this population suggests that it may be prudent to consider alternative surveillance such as colposcopy in similar high-risk populations. Abstract : Alternative surveillance, such as colposcopy, may be prudent in high-risk young women with low-grade Pap smears due to risk of high-grade dysplasia.